Strain gauge basedsensor for real-time truck freightmonitoring - Junpen Tosoongnoen; Khwantri Saengprachatanarug; Khanita Kamwilaisak; Masami Ueno; Eizo Taira; Koichiro Fukami; Karma Thinley (Engineering and Applied Science Research, 2017)
This study aims to develop a weight monitoring sensor for trucks used in sugarcane harvesting. Finite element simulation of the behavior of the load of harvested sugarcane in the bin acting on the truck chassis was established. The position of the weight sensors was determined based on the stress distribution results. The weight sensors were then designed and constructed. A testing unit representing the truck chassis was constructed for calibration of the weight sensors. The results showed that sensors should be installed on the chassis at 180 mm above the rear wheel mounting position, where the maximum stress was 7.64 MPa. The designed weight sensor consisted of four strain gauges attached to the end of two 30 mm diameter bolts. All strain gauges were wired into a Wheatstone bridge circuit (full bridge). A linear relationship between the signals from the sensor and weight was found for weights greater than 1000 N. The weight of sugarcane can be monitored during harvest to do yield mapping and support the combine while it harvests the field.